PENGARUH KUALITAS JASA LAYANAN TERHADAP KEPUASAN KONSUMEN KOTA MAKASSAR - St. Hatidja; Lina Mariana; Arsyad Paweroi; Syarifuddin Syarifuddin (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The purpose of the study is to find out and analyze the influence of service quality consisting of responsiveness, assurance, physical evidence, empathy and reliability on customer satisfaction in Makassar and analyze the dominant service quality affecting satisfaction. The results of the discussion, the results that can be discussed are related to the existence of consumers who get services and are needed as information to find out the identity as respondents and research objects that provide interpretations of respondents' characteristics to analyze the effect of service quality on consumer satisfaction in makassar city. Based on calculations with the help of the SPSS program using the Full Model Regression obtained the multiple liner regression equation is obtained as follows: Y = -3.518 + 0.448X1 + 0.452X2 + 0.309X3 + 0.255X4 + 0.175X5 The regression equation above there is a value of 0 or a constant value of -3.518. This shows that if the independent variable is entirely considered to be worth 0, then consumer satisfaction (Y) is -3,518. This is an indication of the influence of other variables not studied in the analysis of the dimensions of service quality on consumer satisfaction on the Statistical test F or simultaneous significance test, basically showing whether all the free variables included in the model have an influence together on the dependent variable Y. Test F is carried out by comparing the Fhitung with the value of the Ftabel at a real level = 0.05. The F test has a significant effect if the calculation is greater than the Ftabel or the probability of error is less than 5% (P < 0.05). The results of the calculation of the Full Model Regression analysis with the help of the SPSS program. Version 25 obtained a Fhitung of 38,583 with a probability level of 0.000 (significant). Whereas Ftabel is 2.31 thus then Fhitung is greater than Ftabel (38,583 > 2.31) and also probability is much smaller than 0.05, meaning that the hypothesis of this study is acceptable.